A biographical study of Neolithic hoarding: A regional case study of Funnel Beaker Culture hoards from the Southern Limfjord area, Denmark - Sørensen, Casper; Bjørnevad, Mathias; Bye-Jensen, Peter (Danish Journal of Archaeology, 2020)
The tradition of hoarding axeheads is a well-known phenomenon within the first agrarian societies on the North European Plain. Unfortunately, the majority of known hoards have been found as stray finds or under circumstances with poor or no documentation, leading to considerable source critical issues. However, in this paper we analyze four hoards that have either been professionally excavated or have had their find circumstances recorded and are all found within the same geographical area along the southern Limfjord region of Denmark. The detailed contextual information of these hoards is used as a foundation for interpreting these hoards and question the oft-repeated dualistic categorization of hoards as wetland or dryland phenomena. The analytical method employed in this study uses micro- and macroscopic observations to create biographies for the axeheads and to so shed new light on hoarding practices. This approach challenges the previous macro-scale approaches. The results in the study provide a detailed insight on production, use-life, exchange and deposition of axeheads in hoards within the TRB. The aim of the paper is to forward this analytical approach and to offer a fresh perspective on the TRB hoards. In concluding, avenues for future research and debate are sketched out.